The Gospels and their receptions: Festschrift Joseph Verheyden - Jonge, Henk Jan de; Grundeken, Mark; Kloppenborg, John S.; Tuckett, Christopher M.; Verheyden, Joseph (Bibliotheca Ephemeridum Theologicarum Lovaniensium Ser., 2022)
"With this volume twenty-seven friends and colleagues of Joseph Verheyden, Professor of New Testament at KU Leuven, celebrate his sixty-fifth birthday and honour him for his outstanding achievements in the study of the New Testament and early Christian literature. The contributions, written by authors from many countries in Europe, Canada, the United States, and South Africa, discuss the origin of the earliest gospels, the Sayings Source Q, various solutions to the Synoptic Problem, and the textual transmission of the canonical gospels. Other essays examine pre-Markan traditions, the traces the canonical gospels have left in the Apostolic Fathers, and the reception of the gospels in non-canonical writings such as the Gospel of Peter, the Apocalypse of Peter, and the Acts of Thecla, and in patristic and gnostic literature. Several papers are detailed commentaries on specific passages in the New Testament gospels, or concentrate on such figures as Mary, the mother of Jesus, and Nathanael. The volume also includes Verheyden's full bibliography 1979-2022."